“Sequencing Matters”: Investigating Suitable Action Sequences in Robot-Assisted Autism Therapy - Baraka, Kim; Couto, Marta; Melo, Francisco S.; Paiva, Ana; Veloso, Manuela (Frontiers in Robotics and AI, 2022)
Social robots have been shown to be promising tools for delivering therapeutic tasks for children with Autism Spectrum Disorder (ASD). However, their efficacy is currently limited by a lack of adaptation and personalization of the robot’s social behavior to successfully meet therapeutic and interaction goals. This paper investigates the effect of different robot action sequences in structured tasks targeting attention skills, in the context of a social interaction with children with different ASD profiles. Based on an autism diagnostic tool, we devised a robotic prompting scheme on a NAO humanoid robot, aimed at eliciting target behaviors from the child, and integrated it in a novel interactive storytelling scenario involving screens. We programmed the robot to operate in three different modes: diagnostic-inspired (mode Assess), personalized therapy-inspired (mode Therapy), and random (mode Explore). Our exploratory study with 11 young children with ASD highlights the usefulness and limitations of each mode according to the interaction goals, and paves the way towards more complex methods for balancing short-term and long-term goals in personalized robot-assisted therapy.